PENERAPAN MODEL STAD UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 17 PIDIE - Gusti Handayani; Muna Suraiya (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2020)
This study aims to improve student learning outcomes by implementing the STAD model in 4th grade students of MIN 17 Pidie. This type of research is Classroom Action Research (CAR) with the research subjects were 35 of the 4th grade students of MIN 17 Pidie. Data collection techniques in this study were carried out using observation sheets, tests, and documentation. The application of the STAD learning model was carried out through seven stages, which are: (1) conveying learning objectives and motivating students, (2) presenting learning materials, (3) forming heterogeneous groups consisting of 4-5 students, (4) guiding group cooperation in completing assignments or LKPD, (5) giving quizzes or individual tests, (6) calculating individual progress scores based on improvements in learning outcomes, and (7) giving awards to groups that obtained the best scores. The results of the study showed that in cycle I, the average score was 62.28. There was an increase in cycle II of 69.28 and increased again in cycle III of 90. It can be concluded that the application of the STAD model can improve the learning outcomes of 4th grade students of MIN 17 Pidie.